Submicron carbon-based hybrid nano-pour-point depressant with outstanding pour point depressant and excellent viscosity depressant - Xinlei Jia; Mingming Fu; Xueyang Xing; Lixin Wei; Yang Song; Lin Zhang; Xiaoheng Geng; Haiying Guo (Arabian Journal of Chemistry, 2022)
We have investigated the effective utilization potential of carbon nanomaterials in the field of pour point depressants, and reported three kind of carbon-based hybrid nano-pour-point depressants with different dimensions. In this paper, poly-α-olefins-acrylate high-carbon ester pour point depressant (PAA-18) was prepared by esterification and polymerization as the basic pour point depressant. Then, the basic pour point depressant PAA18 was modified by solvothermal method with graphene oxide (GO), carbon nanospheres (Cna) and carbon nanotubes (OCNTs). The morphology and structure of the composites were analyzed by SEM, FTIR and XRD. The results showed that PAA18 was successfully in situ polymerized on GO, Cna and OCNTs. We took the simulated oil as the experimental object, and evaluated its pour point, rheological properties and wax crystal morphology, and achieved excellent results. In the three carbon-based hybrid nano-pour-point depressants with different carbon contents, the oxidation carbon nanotubes composite pour point depressant (PAA18-1 % OCNTs) with carbon content of 1 % had the best pour point and viscosity reduction effect when the dosage was 1250 ppm, which could make the pour point of the simulated oil containing wax decrease by 16 °C. PAA18-1 % OCNTs reduced the pour point by 5 °C more than PAA18. This paper provides reference for the application of carbon nanomaterials in the field of pour point depressant.